PENGARUH KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Gustiandika, Tito; Hadiprajitno, P. Basuki (Diponegoro Journal of Accounting, 2014)
This research aim for testing by empirical methode such as (1) influence of investment decision to corporate values, (2) influence of financing decition to corporate values, (3) influence of Corporate Governance (CG) application to corporate values, (4) influence of investment decision to CG corporate values as moderating variable, and (5) influence of financing decision to CG corporate values as moderating variable. Independent variable that is used in this research is corporate values and CG as moderating variable.Corporate sample in the research are corporate that have score at CGPI with observation periode is 2007 to 2011. Purposive sampling methode used to collect the data for this resarh and it use 46 corporate and this research use multiple regression for data analysis.Result from this research are (1) investment decision have positive influence to corporate values, (2) financing decition have positive influence to corporate values, (3) Corporate Governance have positive influence to corporate values, (4) Corporate Governance do not have moderating efect in the moderation of investment decision influence to corporate values, (5) Corporate Governance have moderating efect in moderation of positive from financing decition to corporate values.